2021
DOI: 10.36834/cmej.69298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical therapy and occupational therapy student placements on productivity: a scoping review

Abstract: Introduction: Clinical educators may perceive that student supervision is time consuming and reduces productivity. This perception is in contrast to research conducted in the 1990’s that found students do not negatively impact productivity. There is a need to review the current literature on this topic as a result of health care cost-containment measures that emphasize efficiency. The purpose of this scoping review was to map and examine the impact of physical and occupational therapy student placements on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…26,27 Although recent studies noted productivity increases during some CE experiences, variance in CE practices, CI experience, and student characteristics also led to productivity decreases. [28][29][30][31] erefore, increased collaboration with academic partners to promote and support successful CE experiences is warranted.…”
Section: Challenges For Clinical Education Facultymentioning
confidence: 99%
“…26,27 Although recent studies noted productivity increases during some CE experiences, variance in CE practices, CI experience, and student characteristics also led to productivity decreases. [28][29][30][31] erefore, increased collaboration with academic partners to promote and support successful CE experiences is warranted.…”
Section: Challenges For Clinical Education Facultymentioning
confidence: 99%
“…Although other studies have indicated that student programs significantly increased productivity in the acute care setting, these studies were not performed at a time that required additional training and widespread considerations as needed during the COVID-19 pandemic. 24,26,27 erefore, this era, both during and immediately postpandemic, requires additional support systems and training to ensure effectiveness and efficiency in patient care. ese support systems and training include increasing student preparedness, which CIs cited as a key factor in their willingness to serve.…”
Section: (9)mentioning
confidence: 99%